Palliative Hope as a Responsible Dialogically Lived Relation between Religion and Medicine - Vadíková, Katarína Mária (IDEAS. PHILOSOPHICAL JOURNAL. SPECIAL SCIENTIFIC ISSUES, 2019)
The article deals with the contribution of Vrana, Guardini, Wojtyła, Marcel in the formation of foundational provisions of Christian dialogical humanistic ethics. Author focuses on heuristic analysis of the relationship of religion and medicine in relation to the challenge of personal conscience to personal responsibility in palliative care conditions. The main result of the analysis of article is the term palliative hope, the application of which is conditional on responsible dialogue, the live relationship between religion and medicine, without requiring special education in the field of religion or medicine. Palliative hope means a specifically human ability to share suffering in a personal dialogue meeting, not necessarily mentioned but the inevitable participation of God, which results in confidence in the best to come – for the good